Growth promoter effect on the Botryococcus braunii Kutzing 1849 culture by several different bacterial strains (2017)
ABSTRACT: There are several strategies to improve the growth of microalgae in industrial processes. In recent years, one of them has gained strength to achieve this goal: the co-culture with bacteria. Using growth-promoting substances, producer bacteria enhance microalgae biology activity, similar to how they have been used to promote the successful production of crops. The aim of this study was to evaluate the promoter capacity of strains Bacillus subtilis, Corynebacterium aquatile and Flavobacterium aquatile, evaluate their ability to improve the growth rate of microalgae Botryococcus braunii and to optimize the process derived from its cultivation. This study showed that the tested bacteria were able to increase up to 1.7 times the B. braunii growth rate and this promoting ability remained present in cell lysate preparations from the same bacterial strains.